2021
DOI: 10.1038/s41565-021-00923-2
|View full text |Cite
|
Sign up to set email alerts
|

Cell-mimicking nanodecoys neutralize SARS-CoV-2 and mitigate lung injury in a non-human primate model of COVID-19

Abstract: Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has grown into a global pandemic, and only a few antiviral treatments have been approved to date. Angiotensin-converting enzyme 2 (ACE2) plays a fundamental role in SARS-CoV-2 pathogenesis because it allows viral entry into host cells. Here we show that ACE2 nanodecoys derived from human lung spheroid cells (LSCs) can bind and neutralize SARS-CoV-2 and protect the host lung cells from infection. In mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
121
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(123 citation statements)
references
References 34 publications
2
121
0
Order By: Relevance
“…Recently, cell membrane–coated nanodecoys have shown great promise for cytokine/antibody clearance and toxin neutralization through interactions with membrane proteins ( 36 39 ). These cell membrane–coated nanodecoys that inherit the antigenic profile of the source cell can absorb and neutralize pathological molecules ( 37 , 40 42 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, cell membrane–coated nanodecoys have shown great promise for cytokine/antibody clearance and toxin neutralization through interactions with membrane proteins ( 36 39 ). These cell membrane–coated nanodecoys that inherit the antigenic profile of the source cell can absorb and neutralize pathological molecules ( 37 , 40 42 ).…”
Section: Introductionmentioning
confidence: 99%
“…To theoretically optimize this antiviral nanoformulation, they used molecular docking and dissipative particle dynamics (DPD) simulations to computationally investigate the drug-carrier interactions and their assembly process. They verified the strong interactions between Dnase-1-coated PD-PEG NPs 220 Suppress neutrophil activities and cytokine storm [106] Nanodepot of manganese (Mn 2+ ) 35 Release Mn 2+ to promote IFN response [111] Abbreviations. PD-PEG: polydopamine-poly(ethylene glycol); Dnase-1: deoxyribonuclease I; PAMAM: polyamidoamine.…”
Section: Nanoagents Interfering Viral Replicationmentioning
confidence: 87%
“…Nanodecoys enable customization with various types of cellular vesicle components. Li et al reported that ACE2 nanodecoys derived from human lung spheroid cells (LSCs) neutralized COVID-19 and mitigated lung injury [178]. Furthermore, LSC-nanodecoys promoted viral clearance and reduced lung injury via inhalation administration.…”
Section: Viral Inhibitionmentioning
confidence: 99%